Thinking International Relations as a Global Discipline - Brenes-Porras, Celestina (2021)
This book analyzes three main topics: the institutionalization of the IR's theory, theory formulation, and the future of International Relations as a discipline. Besides, it is possible to identify two macro narratives regarding the dependence on Occidental thinking and the emerging of new epistemic perspectives in this field.